A Comparative Study of Criteria for Notifying the Patients about the Risks of Treatment in American, French, English and Iranian law - Omid Nasrollahi Shahri; Hojjat Mobayen; Mohammad Ali Khorsandian; omid asemani (پژوهش های حقوق تطبیقی, 2023)
According to the governing principles of medical law, the doctor's intervention in the patient's treatment requires the informed consent of the patient. This consent is achieved when the patient has expressed her/his consent by having sufficient information about the treatment process and its risks. In this study, the question related to the issue that what risks the doctor should inform the patient is answered by a descriptive-analytical method and a comparative approach in American and French law. Despite the different approaches, the two main criteria of "importance of risk" and "probability of risk" are the most fundamental influencing factors in determining the scope of the doctor's commitment in informing about the risks of treatment. In French law, based on the types of risk, "serious" and "common" risks are recognized as the subject of the doctor's obligation to inform, but in American law, based on the approach founded on the patient's perspective and with objective criterion, the doctor is obliged to inform about the risks that are typically important and basic from the patient's point of view, according to the "severity of the risk" and the "percentage of its occurrence". The new approach of English law is also an integrated approach based on "active interaction between doctor and patient" which, due to attention to the specific characteristics and conditions of the patient under treatment, brings maximum efficiency to realize informed consent. The same approach is also suggested in Iran law, which means that before treatment, the doctor, by examining the patient's condition, mood and views, in an active interaction, recognize important risks from the patient's point of view, and in cases where access to the patient's point of view, it was not possible to use the criterion of the reasonable patient.